2004
DOI: 10.1023/b:qure.0000040783.94127.a3
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Coronary Heart Disease Compared to Norms in Spanish Population

Abstract: The comparison between HRQL in coronary patients and that in the general population confirms the impact of the disease especially in the youngest patients, and allows intervention to be directed towards the more vulnerable groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
2
23
0
3
Order By: Relevance
“…Our finding that younger CHD patients tend to have more severely impaired HRQoL than the oldest group (Ն65 years of age), especially in health utility and self-rating of health, is consistent with previous research. 25 This difference may be partially explained by the fact that CHD has a much bigger impact on patients who are at their most productive age than those who are retired. Adjustment or coping mechanisms also may contribute to this difference, particularly for overall health perception.…”
Section: Discussionmentioning
confidence: 93%
“…Our finding that younger CHD patients tend to have more severely impaired HRQoL than the oldest group (Ն65 years of age), especially in health utility and self-rating of health, is consistent with previous research. 25 This difference may be partially explained by the fact that CHD has a much bigger impact on patients who are at their most productive age than those who are retired. Adjustment or coping mechanisms also may contribute to this difference, particularly for overall health perception.…”
Section: Discussionmentioning
confidence: 93%
“…Thus researchers have suggested that using the SF-36 Vitality scores of the general population as reference data is a valid approach for establishing cutoff scores on measures of fatigue [21]. In order to indicate significant healthrelated limitations, previous studies [23][24][25] dichotomized the Vitality scale based on the 25 th percentile. That is, individuals scoring at or below the 25 th percentile were considered to be experiencing limitations due to fatigue while those scoring above the 25 th percentile were not considered to be suffering such limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies assessing HRQoL in patients with CAD have been carried out in the United States (6)(7)(8) , European countries (5,(9)(10) and a smaller number of studies have been conducted in countries like Canada (11) . Their assessments of HRQoL have been largely based on the Medical Outcomes Study: 36-Item Short Form Survey (SF-36) questionnaire and researchers have conducted these assessments at different time points after first hospital admission due to CAD (7,(9)(10)(11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of HRQoL between individuals from the general population and those with CAD has shown that the latter have lower scores in both physical and emotional aspects when compared to those without CAD (5)(6) .…”
Section: Introductionmentioning
confidence: 99%